Evaluation of Thrombolytic Potential of Elaeagnus rhamnoides (L.) A. Nelson - Rehman, Ayesha; Hussain, Shabbir; Ahmad, Muhammad; Riaz, Muhammad; Amin Abid, Muhammad; Gulab Shazady, Tanzeela (Scientific Inquiry and Review, 2022)
Plants find a special significance in the field of medicine due to their therapeutic value. Thrombolytic agents play a crucial role in the treatment of numerous human diseases including atherothrombotic diseases, pulmonary embolism, and myocardial infarction. The current study was performed to evaluate the thrombolytic potential of Elaeagnus rhamnoides (L.) A. Nelson (Sea buckthorn or SBT). The extract of leaves, stems, and berries of the investigated plant displayed 28%, 26%, and 44% blood clot lysis, respectively as compared to that of a standard thrombolytic agent namely streptokinase (59% lysis). The fruit extract of sea buckthorn was found to display higher thrombolytic potential as compared to that of its leaves and stem. It was concluded that the extract of leaves, stem, and berries of SBT may find applications in the future as a thrombolytic agent. The presence of important functional groups for instance, alcohol, aldehyde, alkyne, alkene, amines, and ester in different ariel parts of SBT were verified by FTIR spectroscopy.